Answer :

sqdancefan

Answer:

  (x, y) = (5, 7)

Step-by-step explanation:

It can be useful to put these equations into standard form, with mutually-prime coefficients and a positive x-coefficient.

  10x +y -(4x +4y) = 9 . . . . . subtract the variable terms on the right

  6x -3y = 9  . . .  simplify

  2x -y = 3 . . . . . divide by 3 to put in standard form

__

  (x +10y) -(10x +y) = 18 . . . . . subtract the variable terms on the right

  -9x +9y = 18  . . .  simplify

  x -y = -2 . . . . . . . divide by -9 to put in standard form

__

Now, we can subtract the second equation from the first.

  (2x -y) -(x -y) = 3 -(-2)

  x = 5

  y = x+2 = 7 . . . from the second simplified equation

The solution is (x, y) = (5, 7).

${teks-lihat-gambar} sqdancefan

Other Questions